Determinación de los efectos ambientales provocados por la contaminación de vertidos y descargas de aceites, grasas y lubricantes provenientes de las lubricadoras, ubicadas en la lotización gonzález; que afectan al estero orienco de la parroquia nueva loja, cantón lago agrio y propuesta del plan de manejo ambiental - Ortiz Tubón, Jonathan Edgar (2016)
The objective of the present study was to identify and evaluate the possible environmental impacts generated by the oil change activities of the Lubrioro and Coplago lubricators that affect the Orienco estuary located in the González, Nueva Loja parish. Through an environmental diagnosis, information was collected from the study area, field visits to identify the physical, biotic and socioeconomic components, soil and water samples in each of the lubricators. For the identification of aspects and impacts, environmental valuation matrices were used, with the following results: 13 environmental impacts evaluated correspond to 47% of the "very significant" negative impacts, the most important impact evaluated in the oil change activity was The impact on the quality of the water by the spillage of used lubricating oil, an impact caused by the analysis of the water sample in the oil and grease parameter giving a value of 1.20 mg / L in the Coplago lubricator and 5.60 mg / L in the Lubrioro lubricator whose values do not meet the permissible maximum limit TULSMA Book VI Annex 1 Table 12; In the complementary activities nine environmental impacts were evaluated, of which 78% correspond to the alteration of water quality by generation of liquid discharges with waste oil used. Therefore, in the present study, an Environmental Management Plan is proposed that allows the control, mitigation and prevention of the possible impacts generated by the activities of the lubricators.